“The most charming Romanesque mosaic”: iconografia e restituzione grafica del mosaico pavimentale di San Tommaso ad Acquanegra sul Chiese - Vaccaro, Maddalena (Hortus Artium Medievalium, 2014)
Abstract The figured mosaic pavement in San Tommaso in Acquanegra sul Chiese (eleventh-twelth centuries) is the main subject of the analysis. The church is a former Benedectine abbey and still preserves Romanesque architectural structures and wall paintings, in addition to the mosaic floor defined as «the most charming» by A.K. Porter. Firstly, a map of mosaic fragments and renderings in a 3D reconstruction of the church are presented. Then the analysis focuses on the iconographic subjects and their semantic value, investigated with references to the written culture i.e. Christian literature, classical texts or astronomic and naturalistic treatises. Comparisons to others mosaic pavements and other figurative sources, such as illuminated manuscripts, are given as well. Finally, relationships between figural themes and to architectural and functional spaces are considered: the results suggest that mosaic figures contribute to the ‘hierarchy’ of the spaces in the church, creating a complex image-system.